3β-Hydroxy-5β-hydroxy-B-norcholestane-6β-carboxaldehyde (SEC-B) Induces Proinflammatory Activation of Human Endothelial Cells Associated with Nitric Oxide Production and Endothelial Nitric Oxide Synthase/Caveolin-1 Dysregulation - Maria Gemma Nasoni; Serena Benedetti; Rita Crinelli; Francesco Palma; Barbara Canonico; Francesca Monittola; Chiara Zerbinati; Luigi Iuliano; Francesca Luchetti (MDPI AG, 2022)
Oxysterols are a family of 27-carbon cholesterol oxidation derivatives found in low-density lipoproteins (LDLs) and atherosclerotic plaques where they trigger several biological responses involved in the initiation and progression of atherosclerosis. Several pieces of evidence suggest that oxysterols contribute to endothelial dysfunction (ED) due to their ability to alter membrane fluidity and cell permeability leading to inflammation, oxidative stress and apoptosis. The present study aimed to investigate the molecular events occurring in human microvascular endothelial cells (HMEC-1) in response to autoxidation-generated 3β-hydroxy-5β-hydroxy-B-norcholestane-6β-carboxaldehyde (SEC-B) exposure. Our results highlight that SEC-B rapidly activates HMEC-1 by inducing oxidative stress, nitric oxide (NO) production and pro-inflammatory cytokine release. Exposure to SEC-B up to 24 h results in persistent accumulation of the vasodilator NO paralleled by an upregulation of the endothelial nitric oxide synthase (eNOS) enzyme and downregulation of Caveolin-1 (Cav-1) protein levels. Moreover, reduced expression and extracellular release of the vasoconstrictor factor endothelin-1 (ET-1) are observed. Furthermore, SEC-B stimulates the expression of the cytokines interleukin-6 (IL-6) and tumor necrosis factor-like weak inducer of apoptosis (TWEAK). This proinflammatory state leads to increased monocyte recruitment on activated HMEC-1 cells. Our findings add new knowledge on the role of SEC-B in ED and further support its potential implication in atherosclerosis.